2018
DOI: 10.1590/1678-5150-pvb-5034
|View full text |Cite
|
Sign up to set email alerts
|

Atividade antibiofilme de substâncias de Croton urucurana em Staphylococcus aureus isolado de mastite bovina

Abstract: RESUMO: A mastite bovina é a enfermidade que causa maior impacto na produção leiteira, sendo o microrganismo Staphylococcus aureus o mais prevalente. Este gênero possui a capacidade de produzir biofilmes que é um importante mecanismo de resistência aos antibióticos. Considerando a capacidade terapêutica das plantas, a espécie Croton urucurana, nativa do Cerrado, foi alvo do presente estudo, que teve como objetivo avaliar a atividade antibiofilme in vitro do extrato vegetal e substâncias isoladas desta espécie,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…The Non- aureus CoPS treatment is carried out in drying and has good responses to conventional dry cow therapies, since Staphylococcus aureus is the causative agent of mastitis with the lowest percentage of cure, due to its protective barrier, which is the ability to form an abscess inside the mammary gland, making the action of antibiotics difficult, in addition to being methicillin resistant bacteria, their treatment is carried out in the drying process with the use of an intramammary antibiotic associated with an injectable [ 6 , 12 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The Non- aureus CoPS treatment is carried out in drying and has good responses to conventional dry cow therapies, since Staphylococcus aureus is the causative agent of mastitis with the lowest percentage of cure, due to its protective barrier, which is the ability to form an abscess inside the mammary gland, making the action of antibiotics difficult, in addition to being methicillin resistant bacteria, their treatment is carried out in the drying process with the use of an intramammary antibiotic associated with an injectable [ 6 , 12 ].…”
Section: Discussionmentioning
confidence: 99%
“…Antimicrobial resistance is the ability of a microorganism to grow or survive in the presence of an antimicrobial at a concentration that is generally sufficient to inhibit or kill microorganisms of the same species [ 20 ]. Nader et al [ 6 ] reported in their work that the indiscriminate use of antimicrobials, with the wrong concentration, dosage or application interval, has increased and accelerated this resistance process, making it a serious threat to public health. One of the main causes of antimicrobial resistance in dairy cattle is the fact that it is associated with the use of antibiotics for the treatment of mastitis, whether in the lactation phase or in the drying process of the animal, associated with its erroneous use in the production [ 12 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The search for plant products as antimicrobial agents has increased due to the emergence of resistance to conventional antibiotics and sanitizers, as well as the high cost of developing new synthetic molecules. Plants with demonstrated antimicrobial properties are being targeted for the development of new drugs that can overcome microbial resistance and are economically viable, showing promising results (GUIMARÃES, 2010;NADER et al, 2018). Brazil is one of the leading countries in milk producer and exporter.…”
Section: Introductionmentioning
confidence: 99%